IoT-Based Electricity and Lecture Room Usage Management Information System at State University of Surabaya - Muhammad Irfan Jazuli; Bonda Sisephaputra (Universitas Negeri Surabaya, 2026)
The demand for electrical energy in university environments continues to increase in line with the growing number of students and the intensified use of various facilities. This condition has the potential to cause energy waste, especially in lecture rooms. This situation may lead to an increase in the University's operational costs, which could ultimately disrupt the allocation of budgets for various academic and non-academic activities. Therefore, a solution is needed that can monitor and control energy usage more efficiently. This study aims to design an ESP32 and RFID-based device for implementing IoT technology in classroom electricity and room management systems, as well as to develop an IoT-integrated room management system. The research method includes the design of hardware using ESP32, RFID RC-522 module, relay, push button, buzzer, solenoid door lock, and I2C LCD, connected to a web-based application built with Laravel as the backend for authentication, data management, and room usage monitoring. Tests were conducted to measure E-KTP identification accuracy, scanning speed, check-in and check-out success rates, and the integration between hardware and the web system. The results show that all E-KTPs were successfully identified with a 100% success rate, with an average scanning time of 0.682 seconds during registration, 0.728 seconds during check-in, and 0.775 seconds during check-out, with a maximum scanning distance of 1 cm. The system can also display real-time room usage data on the admin dashboard and control electrical devices according to room booking status. Thus, the developed system is not only effective in authenticating room access and monitoring electricity usage but also contributes to reducing energy waste and supporting efficient and sustainable classroom management in higher education institutions.